Międzynarodowe życie rzeczy. Wprowadzenie - Gałganek, Andrzej (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2014)
The main goal of this article isintroduction to the Actor-Network Theory (ANT) to raise questions about its role in International Relations. While concepts of ANT are very promising we propose to treat ANT as a new theoretical model for international relations scholarship. ANT argues us to recognize that such things as currency, weapons, computers, ships, silk, and others objects are inherent part of international relations. The interest of ANT in International Relations reflects a growing dissatisfaction with the cultural reductionism (constructivism) and methodological nationalism. ANT abandons the dichotomy between the idea and material and argue that such dualisms might prevent us from understanding of international relations. Rejecting this dualisms is to argue for ontological multiplicity of international relations. We initiating in polish International Relations what we hope will be example to bring ANT and International Relations into conversation.
International life of things. Introduction